2019
DOI: 10.1016/j.ces.2019.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism and kinetics for Pt/CNTs catalyzed base-free oxidation of glycerol

Abstract: Fundamental understanding of heterogeneously catalyzed aerobic, base-free oxidation of glycerol is highly desirable for sustainable and highly efficient chemical synthesis. In this work, Pt/CNTs catalyzed base-free oxidation of glycerol is investigated by combining experiments, DFT calculations and kinetics analysis. The solvent effects and kinetic isotope effects measurements as well as DFT calculations reveal that water-assisted O2 activation to form active OH* intermediates is not in rate-determining step (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…This activation energy in the AuPt (111) model (3.56 kcal/mol) is only slightly lower than that in the Pt (111) model (3.27 kcal/mol). It has been reported that MgO could also activate the OH bond, thus the energy barrier of this step is probably not affected by the introduction of Au 16,40 . Glycolaldehyde could then be obtained by removing redundant H from CH bond in the CH 2 OHCH 2 O* intermediate (Step‐2).…”
Section: Resultsmentioning
confidence: 99%
“…This activation energy in the AuPt (111) model (3.56 kcal/mol) is only slightly lower than that in the Pt (111) model (3.27 kcal/mol). It has been reported that MgO could also activate the OH bond, thus the energy barrier of this step is probably not affected by the introduction of Au 16,40 . Glycolaldehyde could then be obtained by removing redundant H from CH bond in the CH 2 OHCH 2 O* intermediate (Step‐2).…”
Section: Resultsmentioning
confidence: 99%
“…To unveil the direct function of oxygen vacancies of CeO 2 in the glucose oxidation reaction, kinetic isotope effect (KIE) experiments were conducted by employing H 2 O or D 2 O as the reaction solvent, respectively. 40,41 In order to compare the anti-toxic ability of the catalysts, 10 mM gluconic acid was added at the beginning of the reaction. The KIE values of k H / k D can be obtained based on the slopes of the curves in the initial reaction period for glucose oxidation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the productions of GLYD and GLYA were referred as the conversion of glycerol based on Route I, while that of DHA based on Route II. First, the effects of external mass transfer limitations at the current reaction conditions of stirring speed (700 rpm) and gas flow rate (150 ml·min −1 ) can be eliminated according to our previous work 10 . Moreover, because the catalyst support CNT used here was close‐end and Pt particles mainly located on the external surface of CNT, the effects of internal mass transfer limitations can be also alleviated.…”
Section: Resultsmentioning
confidence: 99%
“…So far, various transformations have been envisaged for glycerol conversion, including hydrogenolysis, oxidation, dehydration, cyclization, halogenation, and pyrolysis, among which the selective oxidation of glycerol has aroused wide interests to produce the high value‐added products 4–8 . Although the two terminal (primary) hydroxyl groups within glycerol are more reactive to produce glyceraldehyde (GLYD) and glyceric acid (GLYA), the secondary hydroxyl is more preferred to be oxidized to produce dihydroxyacetone (DHA) as shown in Figure 1(A), serving as important roles in cosmetics and fine chemical industries 9,10 . Along this line, extensive efforts have been devoted to the catalyst exploration for this selective oxidation reaction, including noble metals (e.g., Ru, Pd, Pt, and Au) and non‐noble metals (e.g., Cr, Mn, Co, Ni, and Cu), and a general consensus is Pt exhibiting relatively higher catalytic activity 11–15 .…”
Section: Introductionmentioning
confidence: 99%